Women's Empowerment Mitigates the Negative Effects of Low Production Diversity on Maternal and Child Nutrition in Nepal - Malapit, Hazel Jean L.; Kadiyala, Suneetha; Quisumbing, Agnes R.; Cunningham, Kenda; Tyagi, Parul (The Journal of development studies, 2015)
We use household survey data from Nepal to investigate relationships between women's empowerment in agriculture and production diversity on maternal and child dietary diversity and anthropometric outcomes. Production diversity is positively associated with maternal and child dietary diversity, and weight-for-height z-scores. Women's group membership, control over income, reduced workload, and overall empowerment are positively associated with better maternal nutrition. Control over income is positively associated with height-for-age z-scores (HAZ), and a lower gender parity gap improves children's diets and HAZ. Women's empowerment mitigates the negative effect of low production diversity on maternal and child dietary diversity and HAZ.